Análise da qualidade de vida, condição bucal, composição salivar e estudo de polimorfismos genéticos em um jovem com Síndrome de Prader-Willi - Michels, Bruna (2020)
Prader-Willi Sydrome (PWS) is a rare, neurobehavioral genetic disorder that alters the individual’s physical and cognitive development. It is a syndrome caused by the loss of activity of the paternal genes expressed on chromosome 15q11-13. This region of chromosome 15 is a complex and with genes that encode numerous proteins, generating many changes, the main ones being related to cardiovascular and respiratory involvement resulting from obesity and directly responsible for high mortality. Although there are descriptions about the systemic and behavioral manifestations of individuals with PWS, there are many doubts about the oral conditions patients with PWS. For this reason, this work aims to describe quality of life, sleep quality, anxiety, quality of life in relation to oral health, identify oral health condition, salivary components and genetic polymorphisms in a 19 year old young man diagnosed with PWS with the intention of contributing to the knowledge of this syndrome. To obtain the results, questionnaires were made with the individual, clinical oral examination, sialometry, sialochemical analysis, and genotyping. As a result, a good cognitive level of the patient was found, quality of life was good or very good, absence of sleep disturbance and moderate anxiety. Regarding oral health, there was a low index of visible plaque and absence of periodontal disease, but the index of decayed, missing or filled teeth was observed above the average of the Brazilian population. There are no changes in salivary variables and genetic polymorphisms have shown base changes in the COMT, FKBP5, PARK2, ANKK1 genes, that have already been associated in the literature with systemic conditions. With the obtained data it was possible to draw a general panorama of the quality of life of the individual with SPW as well as to raise characteristics of oral health in this syndrome.